The Pretrial (Praperadilan) Filed By The Suspect With The Status Wanted List Of People (DPO) - Yuherawan, Deni (Faculty of Law, Pembangunan Nasional Veteran Jakarta University, 2020)
The granting of a Pre-trial petition filed by a suspect whose status is a Wanted List of People (DPO) by the panel of judges is one of the actions deemed to deviate from the rule of law. SEMA Number 1 of 2018 concerning the Prohibition of Proposal for Pretrial by Escaping Suspects or with the status of DPO has confirmed that pretrial applications may not be filed by suspects who have fled or DPO in another sense submitted by legal counsel or their families. In this case, there is a legal problem, namely the conflict of norm values in a rule. So this article is written to analyze whether pretrial filings made by suspects with the status of a Wanted List or DPO can be justified or not. This research is normative legal research that uses a statutory approach (Statute Approach) and a conceptual approach (Conceptual Approach). For this reason, the data that the authors use is secondary data consisting of primary legal materials and secondary legal materials. Primary legal materials consist of legal products such as statutory regulations. Meanwhile, secondary legal materials consist of journals and books that are relevant to research problems. The collected data are then compiled, Â processed, Â and analyzed using prescriptive analysis using substance comparisons so that it will answer the problems.Keywords: Pre-trial, suspect, wanted List of people